Construction Planning Design Of A 5-Storey Building With SAP 2000 v14.0.0 Program In Central Java - Soehartono, Soehartono; Ummi Chasanah (Jurnal Info Sains : Informatika dan Sains, 2025)
The structure of multi- storey buildings basically refers to SNI 1726-2012, SNI 03-1726-2019, SNI 03-2847-2019 and PPPURG 1987. This research aims to determine the calculation of beams and columns using SAP 2000 v14.0.0 and taking into account Earthquake spectrum in Central Java. Central Java is included in the moderate earthquake category, so to avoid structural failure, it is necessary to take into account beam-column connections, and structure modeling as well as calculating the forces acting on the structure with the SAP 2000 v14.0.0 application. The type of material used is concrete f'c = 25 MPa, and reinforcing steel is fy 400 MPa and 240 MPa.